Transversus Abdominis Plane with Rectus Sheath Blocks Versus Port Site Infiltration of Local Anaesthesia in Emergency Laparoscopic Cholecystectomy—Does It Reduce Postoperative Opiate Requirement? A Pilot Study - Sara Izwan; Tanishk Malhotra; Ujvala Vemuru; Michelle Cooper (Surgeries)
Laparoscopic cholecystectomy (LC) is the gold standard of treatments for symptomatic gallstone disease. The aim of this study is to determine if postoperative opiate use is reduced with transversus abdominus plane (TAP) and rectus sheath (RS) regional anaesthetic blocks compared to port site local anaesthetic (LA) infiltration. A prospective, randomised cohort study was conducted of adult patients who underwent an emergency LC between 25 April 2022 and 25 May 2023. An amount of 40 mL of 0.375% ropivacaine was infiltrated as either TAP and RS blocks or to port sites. Patient demographics, operative data, and postoperative opioid use were collected from the medical record. In total, 138 patients were enrolled in this study: 73 patients allocated to the LA to port sites cohort (52.9%) and 65 patients in the TAP and RS cohort (43.5%). The most common indication for surgery was acute cholecystitis. The average amount of opiate analgesia use was 115.2 mg in the LA group compared to 61.2 mg in the TAP and RS group (p < 0.05). Optimisation of postoperative pain allows for early recovery, improved patient satisfaction, and improved cost-effectiveness for the health service. With a trend towards multimodal analgesia, the uptake of TAP and RS regional anaesthesia may help to achieve this goal.